2011
DOI: 10.1021/nl201714y
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Enhanced Energy Transfer between Donor and Acceptor CdTe Nanocrystal Quantum Dot Monolayers

Abstract: Surface plasmon enhanced Förster resonant energy transfer (FRET) between CdTe nanocrystal quantum dots (QDs) has been observed in a multilayer acceptor QD-gold nanoparticle-donor QD sandwich structure. Compared to a donor-acceptor QD bilayer structure without gold nanoparticles, the FRET rate is enhanced by a factor of 80 and the Förster radius increases by 103%. Furthermore, a strong impact of the donor QD properties on the surface plasmon mediated FRET is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
207
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(211 citation statements)
references
References 41 publications
2
207
0
Order By: Relevance
“…Several earlier works have considered the influence of photonic nanostructures on the FRET process: some conclude that the FRET rate depends linearly on the donor emission rate and the LDOS [23][24][25][26][27], while some others report a FRET rate independent of the LDOS [28][29][30][31]. Earlier experiments on aluminum C-shaped nanoapertures did not reveal noticeable changes of the FRET efficiency [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier works have considered the influence of photonic nanostructures on the FRET process: some conclude that the FRET rate depends linearly on the donor emission rate and the LDOS [23][24][25][26][27], while some others report a FRET rate independent of the LDOS [28][29][30][31]. Earlier experiments on aluminum C-shaped nanoapertures did not reveal noticeable changes of the FRET efficiency [32].…”
Section: Introductionmentioning
confidence: 99%
“…6,[19][20][21][22][23][24][25][26][27][28][29] LSP coupled FRET has been observed using single metallic nanoparticles coupled to a single donor-acceptor pair 6 , core-shell structures [23][24][25] and planar structures. [26][27][28] Studying FRET from a conjugated polymer to fluorescent multilayer core-shell NP, Lessard-Viger et al observed a 70% increase in the Förster radius and an increase in the FRET-rate by two orders of magnitude. 24 Also using a core-shell geometry, composed of donor and acceptor fluorophore molecules embedded in a shell coating a Au-Ag core-shell nanocrystal, Wang et al demonstrated that FRET could be switched on and off by varying the spectral position of the LSP resonance relative to the donor emission and acceptor absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the enhancement is believed to arise from the local field enhancement due to the highly localized hot spots produced by the silver nanostructure [8]. Surface plasmon resonance can also be used to enhance luminescence [9] and Förster energy transfer process [10,11]. Since the optical processes depend on the local field strength, strong emphasis has been placed on achieving higher local field enhancement using novel nanostructure geometries.…”
Section: Introductionmentioning
confidence: 99%